Building The Character Of The Millennial Generation In Revolution 5.0 To Realize The Unity Of The Indonesian Nation - Karyono, Hadi; Karno Sabowo, Hudi; Hartati, Sri (International Journal of Educational Research & Social Sciences, 2022)
Building the character of millennials in the era of revolution 5.0 in filling independence is an obligation as a large-populated country such as the Unitary State of the Republic of Indonesia. In facing it, it is necessary to prepare a resilient and characterful generation facing the challenges in revolution 5.0, which is growing at this time, namely applying Pancasila values for the younger generation that can be implemented in the right momentum. In reality, some young people are now damaged by morals because of various things that affect them. Influences include the adverse effects of globalization, friends, increasingly sophisticated electronic media, drugs, liquor, and other harmful things. This research aims to direct the younger generation in building the nation. Research methods using literature studies are data collection techniques by conducting study studies of books, literature, and others. The results of this research confirm that the younger generation at the time of revolution 5.0 still needs direction and understanding in the life of the nation and state. The conclusion is that the younger generation, as the holder of the leadership relay, needs to be equipped with a national character with Pancasila spirit. So that the relay of the continuity of the nation to be maintained by the republic will be the unity and unity of the country and the realization of our national goals.